In vitro Studies and Clinical Observations Imply a Synergistic Effect Between Epstein-Barr Virus and Dengue Virus Infection - Deng, Xiao-Mei; Zhao, Ling-Zhai; Liang, Xue-Ying; Li, Dan; Yu, Lei; Zhang, Fu-Chun; Zhang, Hua; Liu, Zhong-Yu; Xu, Pei (Frontiers in Microbiology, 2021)
Dengue virus (DENV) infection can lead to a complex spectrum of clinical outcomes, ranging from asymptomatic infection to life-threatening severe dengue. The reasons for thus drastically varying manifestations of the disease remain an enigma. Herein, we reported an original discovery of the synergistic effect between pre-existing Epstein-Barr virus (EBV) infection and DENV superinfection in vitro and of a strong correlation of these two viruses in the clinical samples from dengue patients. We showed that I) DENV-2 infection of an EBV-positive cell line (EBV+ Akata cell) reactivated EBV, and it could be blocked by wortmannin treatment. II) examination of human peripheral blood mononuclear cell (PBMC) samples from dengue patients revealed significantly elevated cell-associated EBV DNA copy number at the time of hospitalization versus at the time of disease recovery in most individuals. III) EBV infection promoted DENV propagation in both EBV hosting B cells and indirectly in THP-1 cells, supported by the following evidence: A) EBV+ Akata cells were more permissive to DENV-2 infection compared with Akata cells harboring no EBV virus (EBV- Akata cells). B) Low molecular weight fraction secreted from EBV+ Akata cells could enhance DENV-2 propagation in monocytic THP-1 cells. C) While reactivation of EBV in EBV+ Akata cells further increased DENV-2 yield from this cell line, pharmacological inhibition of EBV replication by acyclovir had the opposite effect. To our knowledge, this is the first investigation demonstrating a positive correlation between EBV and DENV in vitro and in human biospecimens.